Green and blue infrastructure design in a semi-arid region - Bel Fekih Boussema, Safa; Cohen, Marianne; Khebour Allouche, Faiza (Frontiers in Environmental Science, 2022)
The Green and Blue Infrastructure (GBI) is a new approach for dealing with biodiversity conservation based on maintaining the ecological networks by ensuring the survival of animal and plant species. GBI is considered a new public policy to avoid the loss of biodiversity by preserving landscape connectivity and protecting natural habitats from fragmentation. Countries including the United States, Canada, the United Kingdom, Italy, Portugal, Japan, China, Brazil, and Turkey are seeking to integrate this concept into their environmental policies. This study proposed a methodology to design a GBI at a regional scale applied to the Sousse region in Tunisia. Two main approaches were used. The first was based on identifying three reference species marked by different dispersal distances. The second applied GIS spatial analysis using the buffer model to help assess the ecological connectivity. The methodology developed comprises five steps. In the first step, a forest habitat sub-frame, a semi-open habitat sub-frame, and a wetland sub-frame were determined from a detailed land-use map. Then, different biodiversity reservoirs were identified. In the third step, buffers varying between 200, 250, and 300 m depending on the dispersal distance of the reference species (Cape hare, North African Hedgehog, and Marbled Teal) were applied around the reservoirs to identify zones of potential connections between them. Next, buffers were also applied to detect fragmentation zones along road networks and built-up areas. Finally, the ecological corridors were mapped from the overlay between zones of potential connections and the fragmentation map. The result was the creation of a GBI of the Sousse region with reservoirs of biodiversity and ecological corridors connecting them. This methodological approach and the characterization of the Sousse city GBI map represent the first innovative research applied in Tunisia. This prototype can be a reference for other local or regional spaces, contributing toward realizing a national GBI and promoting sustainable projects.